Wang Anshi shi ge yan jiu shi gao Liang Song shi qi = The research of history draft on Wang Anshi's poetry during the Song dynasties - Xu, Tao (Zhonghua shu ju, 2021)
Beschreibung
Literaturverzeichnis Seite 302-326
Keywords: Wang, Anshi / 1021-1086; Wang, Anshi / 1021-1086 / https://id.oclc.org/worldcat/entity/E39PBJwX87PPDXM9mmgjwVgHYP; Chinese poetry / Song dynasty, 960-1279 / History and criticism; Poésie chinoise / 960-1279 (Dynastie des Song) / Histoire et critique; Chinese poetry; Song Dynasty (China); Forschungsbericht